2012
DOI: 10.2174/156800912800190956
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Tailored Treatments with Anti-EGFR Monoclonal Antibodies in Advanced Colorectal Cancer: KRAS and Beyond

Abstract: Personalized medicine emphasizes the practice of considering individual patient characteristics as opposed to that centered on standards derived from epidemiological studies which, by definition, do not take into account the variability of individuals within a given population. When applied to oncology, personalized medicine is an even more complex concept because it extends the variability beyond the individual patient to the individual tumor. Indeed, the great genotypic and phenotypic variability (both in pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 88 publications
0
22
0
2
Order By: Relevance
“…These types of cancer are highly dependent on the epidermal growth factor receptor (EGFR) signaling pathway. Overexpression of EGFR is common in pancreatic adenocarcinoma [31] and novel therapies in metastatic colorectal cancer include antibodies targeted against the EGFR, such as panitumumab and cetuximab [32]. EGFR belongs to the HER family of transmembrane tyrosine kinase receptors, which include HER2 (ErbB2/Neu), HER3 (ErbB3), and HER4 (ErbB4).…”
Section: Introductionmentioning
confidence: 99%
“…These types of cancer are highly dependent on the epidermal growth factor receptor (EGFR) signaling pathway. Overexpression of EGFR is common in pancreatic adenocarcinoma [31] and novel therapies in metastatic colorectal cancer include antibodies targeted against the EGFR, such as panitumumab and cetuximab [32]. EGFR belongs to the HER family of transmembrane tyrosine kinase receptors, which include HER2 (ErbB2/Neu), HER3 (ErbB3), and HER4 (ErbB4).…”
Section: Introductionmentioning
confidence: 99%
“…One fundamental limitation of failed clinical trials is the inability to determine the basis for the lack of efficacy. As strikingly demonstrated in the cases of the targeted agents gefitinib for lung cancer and panitumumab or cetuximab for colon cancer, the likelihood of efficacy is strongly predicted by the presence of epidermal growth factor receptor (gefitinib) or K-Ras (panitumumab and cetuximab) mutations, respectively (37,38). This need for patient selection is likely inherent to the specificity of these targeted agents, compared to the less selective effects of traditional chemotherapy agents.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has demonstrated that miRNAs act either as tumour suppressors by suppressing the expression of target oncogenes, or as proto-oncogenes by inhibiting the expression of tumour suppressor genes (TSGs) (21)(22)(23)(24). Both effects correlate with cancer development and its progression in CRC (11,25,26).…”
Section: Function Of Mirnas In Crcmentioning
confidence: 99%